2020
DOI: 10.1093/ibd/izaa047
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Histologic Inflammation Predicts Colorectal Neoplasia in Ulcerative Colitis: A Validation Study

Abstract: Background Chronic inflammation in ulcerative colitis (UC) is associated with the development of colorectal neoplasia (CRN). A group at St. Mark’s Hospital reported a novel cumulative inflammatory index that predicted the development of CRN in UC patients that we validated with an independent, well-described, matched, case-controlled cohort from the University of Chicago. Methods Cumulative inflammatory burden (CIB) was calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 13 publications
4
24
0
Order By: Relevance
“…[2][3][4][5] Cumulative inflammatory burden scores have been hypothesized to be more direct and reliable predictors for the risk of (a)CRN. Indeed, recent studies support this concept, [41][42][43] although how to construct the optimal cumulative inflammatory burden score is not clear. It can be questioned whether surrogate markers for inflammation should still be used to stratify patients.…”
Section: Summary Of Identified Risk Factors For Advanced Colorectal Nmentioning
confidence: 99%
“…[2][3][4][5] Cumulative inflammatory burden scores have been hypothesized to be more direct and reliable predictors for the risk of (a)CRN. Indeed, recent studies support this concept, [41][42][43] although how to construct the optimal cumulative inflammatory burden score is not clear. It can be questioned whether surrogate markers for inflammation should still be used to stratify patients.…”
Section: Summary Of Identified Risk Factors For Advanced Colorectal Nmentioning
confidence: 99%
“…Future studies will benefit from large cohort sizes, detailed metadata, considerate sample collection and storage techniques, and robust statistical approaches in order to address the many challenges associated with meta-omics research. However, there are studies that show that colon neoplasia is most likely to develop in the setting of active inflammation and is unlikely to develop in the absence of inflammation ( Rubin et al, 2013 ; Shaffer et al, 2021 ; Yvellez et al, 2021 ). The association of meta-omics changes with other non-IBD chronic immune mediated inflammatory diseases suggests that the intestinal microbial milieu may drive systemic inflammation ( Forbes et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous data from St Mark’s have demonstrated that the cumulative burden of inflammation (CIB) in the preceding years can predict the incidence of colonic neoplasia including large non-polypoid LGD, HGD and CRC [HR: 2.1 per 10-unit increase in CIB (equivalent of 10, 5 or 3.3 years of continuous mild, moderate or severe active histological inflammation); 95% CI 1.4 - 3.0; P<0.001] 18 . The predictive ability of the histologic CIB has been recently validated in an external centre 27 . This is in line with the theory that episodic inflammatory insults followed by mucosal healing encourage colonic epithelial cells to acquire carcinogenic genomic instability and mutations, conferring them a survival advantage to clonally proliferate and develop neoplastic lesions 28,29 .…”
Section: Discussionmentioning
confidence: 99%